Estudo do Limiar Nociceptivo durante Privação de Sono utilizando o Potencial Evocado por Laser - Pacheco, Eduardo Azevedo [UNIFESP] (2010)
In the present study, we investigated the effects of total and REM sleep deprivation on the thermal nociceptive threshold using the laser-evoked potential (LEP). Twenty-eight male adult volunteers were randomly assigned to groups of Control (CTRL), Total (T-SD) and REM (REM-SD) sleep deprivation. Pain parameters, such as thermal noxious and warmth thresholds, subjective pain scores as measured by the visual analog scale (VAS) and the objective LEP, were measured daily during the experimental period. Volunteers were automatically stimulated on the dorsum of the hand by blocks of 50 diode laser pulses of 100 ms duration. Intensities increased between successive blocks, ranging from non-noxious to noxious levels. The LEP thresholds were identified in the transitions from no response to the evoked response. The results showed clear and reproducible LEP waves for all the volunteers when stimulated with high intensities, with latencies of the P2 component of the LEP not varying significantly with sleep manipulations. The LEP threshold and the VAS index augmented following SD and were significantly increased after the second night of T-SD. For both SD groups, the mean values of these parameters showed a gradual increase proportional to the sleep deprivation time, followed by a decrease after one night of sleep restoration, but with a stronger analgesic effect for the T-SD group. These observations showed a paradoxical dissociation between LEP threshold and VAS index, with a concomitant hyperalgesic effect and an increase in the LEP threshold, which can be understood by the different effects exerted by sleep deprivation over attention and alert, resulting in different effects on the LEP threshold (nociceptive pathway excitability) and on the VAS index (subjective pain perception).